THE METHODS OF USING DEFINITE AND INDEFINITE ARTICLES IN ENGLISH CLASSES - Yakubova Dilobar Nasritdin qizi; Oʻrayev Botir Sodiqjon oʻgʻli (Web of Journals Publishing, 2024)
The purpose of organizing definite and indefinite articles in English classes is to help you speak and write clearly and without mistakes in English. The main purpose of writing this essay is to learn the rules of the place and use of articles in English and in what situations they are used.
Keywords: English classes, main purpose, without mistake, rules, situations.